1999
DOI: 10.1093/bja/82.4.566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the laryngeal mask airway on oesophageal pH: influence of the volume and pressure inside the cuff

Abstract: We studied gastro-oesophageal reflux (GOR) with a face mask and laryngeal mask airway (LMA), and the effects of inflation pressure and volume of the LMA cuff on oesophageal pH, in 60 patients. Patients were managed with either a face mask (group I) or LMA inflated to obtain a seal in the anaesthesia circuit at 7 cm H2O (group II) or 15 cm H2O (group III). A pH-sensitive probe with two electrodes, 10 cm apart, was placed in the oesophagus during anaesthesia and recordings were made continuously until patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Protrusion of the EGA into the UOS will quite likely contribute to a tight and reliable seal with gastrointestinal tract but may also provoke physiological relaxation reflexes of the lower oesophageal sphincter 18 with a potential reflux of gastric contents. 19 20 Roux and colleagues 19 found an increased incidence of reflux into the distal oesophagus when the cuff of the laryngeal mask airway was inflated to a larger volume, but this was not seen at the level of the mid-oesophagus. It thus appears that not only depth of intrusion into but also the degree of distension of the UOS may affect the relaxation reflex of the lower oesophageal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…Protrusion of the EGA into the UOS will quite likely contribute to a tight and reliable seal with gastrointestinal tract but may also provoke physiological relaxation reflexes of the lower oesophageal sphincter 18 with a potential reflux of gastric contents. 19 20 Roux and colleagues 19 found an increased incidence of reflux into the distal oesophagus when the cuff of the laryngeal mask airway was inflated to a larger volume, but this was not seen at the level of the mid-oesophagus. It thus appears that not only depth of intrusion into but also the degree of distension of the UOS may affect the relaxation reflex of the lower oesophageal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies involving esophageal manometry 7 and lower esophageal pH studies 8 suggest that lower esophageal relaxation occurs during LMA anesthesia. The incidence of silent regurgitation during LMA use is varyingly reported by different groups to be between 0% 9,10 and 80% 11,12 and it has been suggested that this incidence is technique dependent. 13 Proper case selection and optimal techniques of placement as well as the maintenance of adequate levels of anesthesia throughout the procedure have been suggested as important contributory factors in the genesis of regurgitation during LMA anesthesia.…”
mentioning
confidence: 99%
“…This has been confirmed by studies in the distal esophagus 2,7 but it does not appear to be associated with evidence of pH changes in mid-esophagus. 7 A metaanalysis involving 12,901 patients with LMA usage, showed that clinical evidence of pulmonary aspiration using the LMA was comparable to anesthesia administered with an endotracheal tube (ETT). 8 Interestingly, among the full studies reviewed, one of the three patients who aspirated had been in Trendelenburg position with intra-abdominal insufflation.…”
mentioning
confidence: 99%
“…Ce fait a été confirmé par des études de l'oesophage inférieur, 2,7 mais ne semble pas associé à des changements de pH évidents dans l'oesophage médian. 7 Une méta-analyse portant sur 12 901 patients, chez qui on a utilisé le ML, a montré que la preuve clinique d'une inhalation bronchique avec l'usage du ML était comparable à l'anesthésie administrée avec un tube endotrachéal (TET). 8 Fait intéres-sant, parmi toutes les études revues, l'un des trois cas EDITORIAL d'aspiration concernait un patient en position de Trendelenburg chez qui on avait procédé à une insufflation intra-abdominale.…”
unclassified